2018
DOI: 10.1186/s13028-018-0426-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of constant rate infusions of medetomidine–propofol combined with sevoflurane anesthesia in Thoroughbred racehorses undergoing arthroscopic surgery

Abstract: BackgroundThe aim of the present study was to evaluate clinical efficacy of constant rate infusions (CRIs) of medetomidine–propofol combined with sevoflurane anesthesia in Thoroughbred racehorses undergoing arthroscopic surgery. Thirty horses were sedated intravenously (IV) with medetomidine (6.0 μg/kg) and midazolam (0.02 mg/kg) and induced IV with ketamine (1.0 mg/kg) and propofol (1.0 mg/kg). These horses were randomly allocated to three groups and maintained with sevoflurane and CRI of either medetomidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…(32) Cardiopulmonary effects and recovery quality of remifentanil-isoflurane anesthesia in horses [247] (33) Clinical comparison of two regimens of lidocaine infusion in horses undergoing laparotomy for colic [248] (34) Effects of medetomidine constant rate infusion on sevoflurane requirement, cardiopulmonary function, and recovery quality in Thoroughbred racehorses undergoing arthroscopic surgery [249] (35) The cardiovascular status of isoflurane-anaesthetized horses with and without dexmedetomidine constant rate infusion evaluated at equivalent depths of anaesthesia [250] (36) Cardiopulmonary effects and anaesthesia recovery quality in horses anaesthetized with isoflurane and low-dose S-ketamine or medetomidine infusions [251] (37) Comparison of the effects of an intravenous lidocaine infusion combined with 1% isoflurane versus 2% isoflurane alone on selected cardiovascular variables and recovery characteristics during equine general anaesthesia [252] (38) Clinical usefulness of intravenous constant rate infusion of fentanyl and medetomidine under sevoflurane anesthesia in Thoroughbred racehorses undergoing internal fixation surgery [253] (39) Effect of detomidine or romifidine constant rate infusion on plasma lactate concentration and inhalant requirements during isoflurane anaesthesia in horses [254] (40) Clinical comparison of dexmedetomidine and medetomidine for isoflurane balanced anaesthesia in horses [255] (41) Clinical evaluation of constant rate infusion of alfaxalone-medetomidine combined with sevoflurane anesthesia in Thoroughbred racehorses undergoing arthroscopic surgery [256] (42) Clinical effects of constant rate infusions of medetomidine-propofol combined with sevoflurane anesthesia in Thoroughbred racehorses undergoing arthroscopic surgery [257] (43) Plasma concentrations at two dexmedetomidine constant rate infusions in isoflurane anaesthetized horses: A clinical study [258] 2 (44) Hemodynamic function during neurectomy in halothane-anesthetized horses with or without constant dose detomidine infusion [259] (45) Combination of continuous intravenous infusion using a mixture of guaifenesin-ketamine-medetomidine and sevoflurane anesthesia in horses [260] (46) Evaluation of a mixture of thiopental-guafinesine-medetomidine and sevoflurane anesthesia in horses [261] (47) Influence of ketamine or xylazine supplementation on isoflurane anaesthetized horses-a controlled clinical trial [262] (48) Comparative study on sevoflurane anesthesia alone and combined with partial intravenous anesthesia using dexmedetomidine in healthy horses [263] 3 (49) Problems associated with perioperative morphine in horses: A retrospective case analysis [264] (50) Recovery quality after romi...…”
Section: Loe Referencesmentioning
confidence: 99%
“…(32) Cardiopulmonary effects and recovery quality of remifentanil-isoflurane anesthesia in horses [247] (33) Clinical comparison of two regimens of lidocaine infusion in horses undergoing laparotomy for colic [248] (34) Effects of medetomidine constant rate infusion on sevoflurane requirement, cardiopulmonary function, and recovery quality in Thoroughbred racehorses undergoing arthroscopic surgery [249] (35) The cardiovascular status of isoflurane-anaesthetized horses with and without dexmedetomidine constant rate infusion evaluated at equivalent depths of anaesthesia [250] (36) Cardiopulmonary effects and anaesthesia recovery quality in horses anaesthetized with isoflurane and low-dose S-ketamine or medetomidine infusions [251] (37) Comparison of the effects of an intravenous lidocaine infusion combined with 1% isoflurane versus 2% isoflurane alone on selected cardiovascular variables and recovery characteristics during equine general anaesthesia [252] (38) Clinical usefulness of intravenous constant rate infusion of fentanyl and medetomidine under sevoflurane anesthesia in Thoroughbred racehorses undergoing internal fixation surgery [253] (39) Effect of detomidine or romifidine constant rate infusion on plasma lactate concentration and inhalant requirements during isoflurane anaesthesia in horses [254] (40) Clinical comparison of dexmedetomidine and medetomidine for isoflurane balanced anaesthesia in horses [255] (41) Clinical evaluation of constant rate infusion of alfaxalone-medetomidine combined with sevoflurane anesthesia in Thoroughbred racehorses undergoing arthroscopic surgery [256] (42) Clinical effects of constant rate infusions of medetomidine-propofol combined with sevoflurane anesthesia in Thoroughbred racehorses undergoing arthroscopic surgery [257] (43) Plasma concentrations at two dexmedetomidine constant rate infusions in isoflurane anaesthetized horses: A clinical study [258] 2 (44) Hemodynamic function during neurectomy in halothane-anesthetized horses with or without constant dose detomidine infusion [259] (45) Combination of continuous intravenous infusion using a mixture of guaifenesin-ketamine-medetomidine and sevoflurane anesthesia in horses [260] (46) Evaluation of a mixture of thiopental-guafinesine-medetomidine and sevoflurane anesthesia in horses [261] (47) Influence of ketamine or xylazine supplementation on isoflurane anaesthetized horses-a controlled clinical trial [262] (48) Comparative study on sevoflurane anesthesia alone and combined with partial intravenous anesthesia using dexmedetomidine in healthy horses [263] 3 (49) Problems associated with perioperative morphine in horses: A retrospective case analysis [264] (50) Recovery quality after romi...…”
Section: Loe Referencesmentioning
confidence: 99%
“…In our previous study, recovery time to standing was 63 ± 11 min, and recovery score was G5 for 13 horses (52%), G4 for 10 (40%), and G3 for 2 (8%) in Thoroughbred racehorses anesthetized with sevoflurane and medetomidine following premedication with medetomidine (5.0 µg/kg IV), thiopental (4.0 mg/kg IV) and guaifenesin (100 mg/kg IV) [19]. We also reported that recovery time to standing was 40 ± 6 min, and that recovery score was G5 for 7 horses (70%), and G3 for 3 (30%) in Thoroughbred racehorses anesthetized with sevoflurane and medetomidine following premedication with medetomidine (6.0 µg/kg IV), midazolam (0.02 mg/kg IV), ketamine (1.0 mg/kg IV) and propofol (1.0 mg/kg IV) [20]. Due to the different pharmacological interactions of the different combinations of induction agents used, the reason for the significant difference in the quality of recovery between propofol/ ketamine and thiopental/guaifenesin cannot be determined from this study and requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…The addition of butorphanol, 111,112 alfaxalone, 148 propofol, 96 guaifenesin‐ketamine 121,122 or ketamine‐romifidine 120 to PIVA protocols did not improve QR in several studies.…”
Section: Resultsmentioning
confidence: 98%